2018
DOI: 10.3892/ol.2018.8841
|View full text |Cite
|
Sign up to set email alerts
|

α7 nicotinic acetylcholine receptors in lung cancer (Review)

Abstract: Abstract. Lung cancer has one of the highest mortality rates among malignancies globally, and smoking has been documented as the main cause of lung cancer. Nicotinic acetylcholine receptors (nAChRs) were initially identified as notable regulators of the nervous system. In addition to their function in the brain, accumulating evidence indicates that nAChRs perform a host of diverse functions in almost all non-neuronal mammalian cells. The homomeric α7nAChR, a subtype of nAChRs, is responsible for the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 77 publications
0
34
0
2
Order By: Relevance
“…Lung cancer cells endogenously express α7 nAChR, and their activation on these cells leads to stimulation of proliferation [29]. Because acylcholines demonstrated the ability to inhibit nAChR, we hypothesized that they could inhibit proliferation of a lung cancer cell line A549.…”
Section: Acylcholines Inhibit the Viability Of A549 Cellsmentioning
confidence: 99%
“…Lung cancer cells endogenously express α7 nAChR, and their activation on these cells leads to stimulation of proliferation [29]. Because acylcholines demonstrated the ability to inhibit nAChR, we hypothesized that they could inhibit proliferation of a lung cancer cell line A549.…”
Section: Acylcholines Inhibit the Viability Of A549 Cellsmentioning
confidence: 99%
“…In colorectal cancer, the activation of α7nAChR in tumor macrophages inhibits colorectal cancer metastasis through the JAK2/STAT3 signaling pathway (64). α7nAChR has been considered an important drug target for the inhibition of lung cancer (65). On a cautionary note, α7nAChR is such an important neurotransmitter receptor in the CNS and muscle, that targeting nicotinic signaling directly via α7nAChR may cause multiple unwanted side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have indicated a strong link between nicotine/nAChRs and lung cancer risk [34,38]. Nicotine might lead to suppressed apoptosis and cisplatin resistance via α5nAChR/AKT signaling [112].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting nAChRs signaling pathways can significantly attenuate nicotine-associated drug resistance. Several α7nAChR antagonists are potential anticancer drugs [38]. Collectively, studies have suggested that nAChR-induced antiapoptotic effects may play notable roles in drug resistance in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation